Artisan cheese making at home : techniques and recipes for mastering world-class cheeses - Karlin, Mary (Ten Speed Press, 2011)
"A contemporary guide to making 100 artisan cheeses at home--from classic favorites to popular, modern varieties--written by cheese-making authority Mary Karlin. In recent years there has been an explosion in the artisan cheese movement and a kitchen crafting revival. Artisan Cheese Making at Home inspires and encourages do-it-yourselfers with approachable, easy-to-follow instructions to produce mouthwatering cheese at home. From quick and satisfying ricotta and panir to higher payoff cheeses like triple creme camembert, tallegio, and blue gouda--all of the featured cheeses can be made with readily available milks and common kitchen equipment. While most other cheese books take a homey approach to cheese making, this comprehensive, four-color tome embraces the full range of contemporary artisan-style cheeses and is destined to become a modern classic. Written by an experienced cooking teacher and filled with cheese-making tips from some of today's most influential cheese makers, Artisan Cheese Making at Home proves that hand-crafting cheese is not only easy, but also a fascinating and rewarding process"--